How to Develop a Grant Writing Course for Undergraduate Students. Issue 3 (27th March 2023) - Oxford, Julia Thom; Smith, Diane B.; Yarnell, Tracy; Jorcyk, Cheryl L.
Abstract: Grant writing is an important skill to develop, allowing students to envision solutions to issues that impact their local, regional, and global communities. Additionally, grant writing, like other research‐associated activities, can improve student success in and out of the classroom. Grant writing can help students understand the alignment between research activities and a "big picture" understanding of the common good and societal impact of the research. Grant writing can improve students' ability to articulate the significance and broader impacts of research. Faculty mentors can play a major role in grant writing activities by helping to guide undergraduate students through the process. A course‐based approach can help instructors who mentor students in research by providing scaffolding and scheduling tools. This article provides an overview of a grant writing course used as an efficient and effective way for undergraduate students to be guided through the grant proposal writing process with a greater potential for positive outcomes. We discuss why undergraduate students should learn how to write grant proposals, the advantages of teaching grant writing in a course‐based format, time management, learning outcomes, and ways to assess student learning. © 2023 Wiley Periodicals LLC.